حقل التغطية و الستر من أسماء الآلة على وزن فعال و فعالة دراسة صرفية دلالية - بن الشايب, سعيدة, شيماء جمعة (University of El-oued, 2021)
يعتبر اسم الآلة موضوع ذا أهمية في عصر ملئ بالتقدم في العلوم والصناعات ، حيث اخترع الانسان الآلات وابتكر الأدوات، وفيما يتعلق باسم الآلة من حيث مفهومه واشتقاقه وأوزانه ، نجد اختلاف بين اللغويين القدامى والمحدثين في الأوزان السماعية والقياسية، وكل لديه رأي في هذا. وكان من نتائج هذه الدراسة أن ثمت أوزان غير قياسية تزيد نسبتها على الأوزان القياسية التي أضافها المجمع. كما تنوعت أسماء الآلة الدالة على التغطية والستر على وزن فِعال وفِعالة، كخمار وعجار وعمامة وكمامة... وغيرها. كما وردت أسماء الآلة الدالة على التغطية والستر التي جاءت على وزن فِعال أكثر من الأسماء التي وردت على وزن فِعالة. The name of the machine is a topic of importance in an era full of progress in sciences and industries, where man invented machines and invented tools. With regard to the name of the machine in terms of its concept, derivation and weights, we find a difference between the ancient and modern linguists in the audio and standard weights, and everyone has an opinion on this. One of the results of this study was that there were non-standard weights that exceeded the standard weights added by the complex. Also, the names of the instrument indicative of covering and covering an active and effective weight varied, such as the khimar, ajar, the turban, and the muzzle... and others. Also, the names of the instrument indicating covering and covering that came on an active weight were mentioned more than the names that appeared on an effective weigh
Keywords: اسم الآلة* القياسية* السماعية*صيغ اسم الآلة: machine name * standard * audio * machine name formats